Trends in subjective health assesment between 1981 and 2011 as an indicator of persistent social inequalities - Malnar, Brina (Zdravstveno varstvo, 2012)
Background: Historically speaking, public health systems were established to guarantee every citizen equal access to health care and to separate the issue of an individual's health from issues of material welbeing. Using social science methodology, the study set out to explore how successful the welfare system in Slovenia was in achieving this goal during the last three decades, i.e. to what extent social inequalities in Slovenia are being reproduced as health inequalities. Methods: The study is based on six waves of Slovenian Public Opinion surveys carried out between 1981 and 2011 on representative samples of the adult Slovenian population. The main dependent variable is the respondent's selfassessed health and the main independent variable is his or her socio-economic status. The relationship between them was examined using Chi-square tests and regression analysis. Results: The thirty year trend shows persisting inequalities in health as throughout the entire period, self-assessed health is significantly lower at the bottom of the educational and income scale. The largest differences between social strata are observed in the 30 to 60 age group when labour market pressures are most pronounced. Conclusions: The results indicate that inequalities in health are almost impossible to eliminate as long as their deeper causes lie in social inequality. An additional factor that decreases self-assessed health in Slovenia compared to Western Europe is the low level of trust in people and social institutions, which is the likely reason why the relatively favourable statistical picture of social inequalities is not translated into an equally favourable picture of subjective health.
Keywords: Družbena neenakost; Health; Javno mnenje; Public opinion; samoocena zdravja; Slovenia; Slovenija; Social capital (Sociology); Social inequality; Socialni kapital (Sociologija); Zdravje